2020
DOI: 10.1186/s12974-020-01933-y
|View full text |Cite
|
Sign up to set email alerts
|

MCC950, a selective NLPR3 inflammasome inhibitor, improves neurologic function and survival after cardiac arrest and resuscitation

Abstract: Background Cardiac arrest (CA) is associated with high morbidity and mortality, even after spontaneous circulation is re-established. This dire situation is partly due to post-CA syndrome for which no specific and effective intervention is available. One key component of post-CA syndrome is sterile inflammation, which affects various organs including the brain. A major effector of sterile inflammation is activated NLRP3 inflammasome, which leads to increased release of interleukin (IL)-1β. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…Consistent with previous reports that used other CA/CPR models, 16 , 25 we found strong activation of astrocytes and microglia, especially in the hippocampal region, and a considerable number of monocytes and neutrophils infiltrated from the blood into the brain after CA/CPR. Critically, a characteristic immunosuppression phenotype, as revealed in our recent report using a KCl‐mediated CA model, and which is corroborated by clinical immune manifestations, 16 , 27 , 28 , 29 is also evident in young adult and aged mice after asphyxial CA/CPR. We further discovered that in the thymus, the number of double‐positive T cells became largely depleted, and similarly in the bone marrow, the number of B progenitors was massively decreased.…”
Section: Discussionsupporting
confidence: 73%
“…Consistent with previous reports that used other CA/CPR models, 16 , 25 we found strong activation of astrocytes and microglia, especially in the hippocampal region, and a considerable number of monocytes and neutrophils infiltrated from the blood into the brain after CA/CPR. Critically, a characteristic immunosuppression phenotype, as revealed in our recent report using a KCl‐mediated CA model, and which is corroborated by clinical immune manifestations, 16 , 27 , 28 , 29 is also evident in young adult and aged mice after asphyxial CA/CPR. We further discovered that in the thymus, the number of double‐positive T cells became largely depleted, and similarly in the bone marrow, the number of B progenitors was massively decreased.…”
Section: Discussionsupporting
confidence: 73%
“…Novel specific inhibitors of the NLRP3 inflammasome are currently in pre-clinical or clinical trials [382] (ifmthera.com/pipeline). MCC950 (also known as CP-456,773 and CRID-3), a potent inhibitor of NLRP3, promotes microglial clearance of Aβ, reduces Aβ accumulation, and improves cognitive function in APP/PS1 mice [383][384][385][386]. Both MCC950 and Inzomelid, another potent, selective, brain-penetrant NLRP3 inflammasome inhibitor, are expected to move into Phase II trials for a range of disorders, including Parkinson's, Alzheimer's and, motor neurone disease (https://www.europeanpharmaceuticalreview.com/news/1112 01/patents-for-nlrp3-inflammasome-inhibiting-compounds-granted-in-us-and-europe/.…”
Section: Targeting the Inflammasomementioning
confidence: 99%
“…In a colitis mouse model, it was shown that MitoQ suppressed NLRP3 inflammasome activation [ 237 ]. MCC950 is a molecule that inhibits both the canonical and non-canonical inflammasome pathways, preventing its formation [ 258 , 259 , 260 ]. This molecule was shown to reduce neuroinflammation in study models of Alzheimer’s disease [ 238 , 261 ].…”
Section: Therapeutic Strategies Targeting Mitochondria To Fight Infectionmentioning
confidence: 99%